English Teachers' Knowledge in Indonesia - Suryaningrum, Sumarah (MATAI: International Journal of Language Education, 2024)
This study delves into the dynamic and multifaceted realm of English teachers' knowledge, exploring how personal and professional experiences in Indonesian education shape it. Employing a biographical narrative inquiry approach, three elementary school English teachers from Solo, Indonesia, representing different generations, were engaged in detailed interviews. The study reveals the evolving nature of English teachers' knowledge, with one retiring teacher illustrating a shift from traditional to student-centered teaching practices. Another teacher's journey reflects the growing recognition of cultural diversity and the adoption of culturally responsive teaching. The study underscores the significance of continuous professional development and the value of collaborative learning among English teachers of different generations. These findings hold implications for teacher education, professional development, and educational policy, emphasizing the need for context-specific and ongoing support to enhance the quality of teaching in a diverse and ever-changing educational landscape.